2021
DOI: 10.3390/vaccines9020067
|View full text |Cite
|
Sign up to set email alerts
|

Human Transcriptomic Response to the VSV-Vectored Ebola Vaccine

Abstract: Ebolavirus Disease (EVD) is a severe haemorrhagic fever that occurs in epidemic outbreaks, with a high fatality rate and no specific therapies available. rVSVΔG-ZEBOV-GP (Ervebo®), a live-attenuated recombinant vesicular stomatitis virus vector expressing the glycoprotein G of Zaire Ebolavirus, is the first vaccine approved for prevention of EVD. Both innate and adaptive responses are deemed to be involved in vaccine-induced protection, yet the mechanisms are not fully elucidated. A global transcriptomic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(25 reference statements)
2
5
0
2
Order By: Relevance
“…Several ISGs, Dead Box helicases and nucleic acid sensors were acutely induced 3 DPV. Interestingly, this induction was less robust than that observed for VSV-EBOV as indicated by data presented here and published elsewhere (29)(30)(31). In contrast, antiviral innate immune responses in control animals and those that succumb to infection are progressively amplified as disease progresses and are associated with adverse outcomes and high mortality both in NHP and humans (3,4,16,(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 64%
“…Several ISGs, Dead Box helicases and nucleic acid sensors were acutely induced 3 DPV. Interestingly, this induction was less robust than that observed for VSV-EBOV as indicated by data presented here and published elsewhere (29)(30)(31). In contrast, antiviral innate immune responses in control animals and those that succumb to infection are progressively amplified as disease progresses and are associated with adverse outcomes and high mortality both in NHP and humans (3,4,16,(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 64%
“…Library preparation was performed as described in a previous publication ( Santoro et al., 2021 ), using the Ion AmpliSeq™ Transcriptome Mouse Gene Expression Kit from AmpliSeq (Thermo Fisher Scientific), allowing the amplification of 23,930 target genes. Libraries were diluted to 50 pM and pooled in equal volumes (7 μl), with eight individual samples per pool and loaded onto Ion PI™ Chip v3 using the Ion Chef™ Instrument.…”
Section: Methodsmentioning
confidence: 99%
“…The success of the EBOV vaccine produced by Merck Vaccines (rVSV∆G-ZEBOV-GP, marketed as ERVEBO ® ) has provided a strong rationale for efforts to develop other vaccines based on recombinant vesicular stomatitis virus (rVSV) vaccine vector technology [ 12 , 13 , 14 ]. The performance of ERVEBO ® in outbreak environments has clearly shown that the VSV-based technology has multiple features needed for development of other effective filovirus vaccines including, (1) acceptable safety and tolerability; (2) high efficacy after a single dose; and (3) rapid development of protective immunity [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%